GAMBARAN PERILAKU MASYARAKAT DALAM PENCEGAHAN PENULARAN COVID-19 DI KEL. WAJO KEC. MURHUM KOTA BAUBAU - Nurmulya Pertiwi; Nima Meilani; Fitriani (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Coronavirus disease 2019 (COVID-19) is an acute respiratory disease caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). SARS-CoV-2 is a single-stranded RNA (+RNA) enveloped virus belonging to the family Coronaviridae. The working area of the Wajo Public Health Center is the third highest number of Covid-19 cases in 2021, and Wajo Village is the first highest number of Covid-19 cases for the Wajo Public Health Center working area. in the process of controlling the Covid-19 pandemic outbreak. The type of research used is quantitative using a descriptive research design which aims to see an overview of knowledge, attitudes and actions in preventing the transmission of Covid-19. The population in this study is the Wajo Village Community, Murhum District, Baubau City with a total sample of 93 people. The sampling technique used is Simple Random Sampling. Data were collected using questionnaires and data were analyzed using univariate analysis. The results of this study were as many as 93 people (100%%) had good knowledge and none had poor knowledge. As many as 74 people (79.6%) have a good attitude and as many as 19 people (20.4%) have a bad attitude. As many as 19 people (20.4%) had good actions and as many as 74 people (79.6%) had poor actions.